Breast tuberculosis in men: A systematic review. - GianLuca Quaglio; Damiano Pizzol; Anna Bortolani; Fabio Manenti; Petros Isaakidis; Giovanni Putoto; Piero L Olliaro (PLoS ONE)
Setting Breast tuberculosis in male is a rarely reported and poorly described condition. Objective To quantify the number of breast tuberculosis in men, to describe clinical presentation and to present the diagnostic and therapeutic procedures applied. Design A systematic review of the literature including reports published in English, Spanish and French until December 2017. Results The search yielded 26 cases of male breast tuberculosis, median age 56.5 years. Most presented with an isolated breast lump (89%), associated with axillary lymphadenitis (27.8%) and skin inflammation (33.3%). The most common constitutional symptoms were pain (64.7%) and fever (35.3%). Fine-needle aspiration cytology and culture were the most common diagnostic modality (61.5%). Standard anti-tuberculosis regimen was the main treatment, alone or accompanied or preceded by incision and drainage. Conclusions The risk of breast tuberculosis in men appears to be low, but the condition can be difficult to diagnose and the diagnostic delays can be long. Overall prognosis is good following standard anti-tuberculosis regimen with or without incision/drainage.